MUSTAFA SEKİP TUNÇ DÜŞÜNCESİNDE MODEL İNSANI YARATACAK OLAN EĞİTİM ANLAYIŞI - Levent Bayraktar (Felsefe Dünyası)
M. Sekip Tunç is a thinker who combined philosophy with psychology and analyzed events and universe in this context. His concept of man is unified with his idea of the universe and being. Freedom and creativity are the shared concepts of nature and man. Knowledge, culture and values should be passed on man by means of education so that the existence of man should be realized beyond being of a biological creature. Education should unearth the abilities that are potentially available in the individual and should provide him with the opportunity of knowing and developing himself. In this respect, the most salient characteristic of man, in the mind of Mustafa Sekip Tunç, is to be a creative person in harmony with his material and spiritual environment.